Hypnosis Before Wake-up Call? The Revival of Sovereign Credit Risk Perception in the EMU-Crisis - Ingo G. Bordon; Kai Daniel Schmid; Michael Schmidt (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
This paper qualifies the view of pronounced overpricing of sovereign bonds for the so-called GIIPS countries during the financial crisis. We use annual data for 21 OECD countries from 1980 to 2012. As opposed to related studies, our data set allows us to contrast the pricing of macroeconomic fundamentals between three distinct phases: The period before the signing of the Maastricht treaty, the EMU-convergence era, and the financial crisis. In detail, we find: (i) Since the 1980s the role of public debt for the pricing of government bonds has changed twice: Firstly following the signing of the Maastricht treaty, and again with the wake-up call due to the onset of the financial crisis. (ii) Before the financial crisis EMU member countries had - de facto - been perceived as a homogenous group with regard to the role of public debt for sovereign risk pricing. (iii) With the reconsideration of country-specfic fundamentals the role of public debt has not only been revived but its impact upon bond yield spreads has become comparable to the time before the Maastricht treaty.
urn:nbn:de:101:1-201411242627
Keywords: E34; E44; E62; 330; EMU; GIIPS; Public Debt; Risk Perception; Sovereign Bond Yields